Silver-Ruthenium Dioxide Contacts. (1976) - Pedder, D. J.
Abstract : This paper describes the development of a novel electrical contact material, silver-ruthenium oxide, for use in light duty switching applications where low contact resistance values must be maintained. Material fabrication and contact resistance behaviour after exposure to a tarnishing atmosphere are described. An explanation for the low contact resistance values obtained for silver-ruthenium dioxide in comparison with pure silver is offered.